The Use of AI in Medical Writing: Balancing Efficiency and Ethical Responsibility - Yuliana, Yuliana (Proceeding of International Conference on Islamic Education (ICIED), 2025)
The use of artificial intelligence (AI) in medical writing offers many benefits, including increased efficiency and productivity. However, researchers and writers must balance these benefits with the need for ethical responsibility. This paper highlights the balance and efficiency of using AI in medical writing. This is a narrative literature review. Journals were searched from PubMed, ScienceDirect, and Google Scholar. Publication date was within 5 years. There  were 16 articles after screening by keywords, title, abstract, and full text. Researchers and writers must ensure that AI-generated content is accurate, reliable, and free from bias. Transparency about the use of AI tools should be enclosed. The challenges are misinterpretation and bias. Ethical aspects of using AI in medical writing are tranparency, preventing misinterpretation, reliable, accurate, and free from bias. The efficiency of using AI-assited writing is time management. In conclusion, by balancing efficiency and ethical responsibility, researchers can harness the benefits of AI while maintaining the highest standards of ethics and integrity.